Synthesis, Characterization and DNA Binding Studies of N,N′-bis(2-Hydroxy-5-methylbenzylidene)- 2-hydroxy-propane-1,3-diamine Copper(II) and Nickel(II) Complexes - Ramina; Singh, Rajkumar Bhubon; U-wang, Oinam; Singh, Thoudam Surchandra; Jamir, T. Tiakaba (Asian Journal of Chemistry, 2020)
Two new Schiff base transition metal complexes [Cu(HL)]2.CH3CH2OH (1) and [Ni(HL)] (2) (L = N,N′-bis(2-hydroxy-5-methyl-benzylidene)-2-hydroxy-propane-1,3-diamine) were synthesized and characterized by different physico-chemical and spectroscopic techniques. Structure of complex 1 was determined by single crystal X-ray diffractometer. Both the complexes have distorted square planar geometry. The DNA binding study of two complexes was performed via electronic absorption, cyclic voltammetry, photoluminescence, and viscosity methods and found to be intercalative mode of binding.